Inflammation alters myeloid cell and oligodendroglial iron-handling in multiple sclerosis - Christian J. Riedl; Daniel Bormann; Anja Steinmaurer; Anja Novak; Giulia Testa; Elena Poldlehner; Carmen Haider; Thomas Berger; Michael Mildner; Romana Höftberger; Ferdinand Schweser; Simon Hametner (Acta Neuropathologica Communications)
Abstract Changes in brain iron levels are a consistent feature of multiple sclerosis (MS) over its disease course. They encompass iron loss in oligodendrocytes in myelinated brain regions and iron accumulation in myeloid cells at so-called paramagnetic rims of chronic active lesions. Here, we explore the mechanisms behind this overall shift of iron from oligodendrocytes (OLs) to myeloid cells (MCs) and the loss of total brain-iron in MS. We investigated the expression of various iron importers and exporters, applying immunohistochemistry to a sample of control and MS autopsy cases. Additionally, we studied the transcriptional response of iron-related genes in primary rodent OL progenitor cells (OPCs) and microglia (MG) to various combinations of known MS-relevant pro-inflammatory stimuli together with iron loading. Histologically, we identified a correlation of OL-iron accumulation and the expression of the ferritin receptor TIM1 in myelinated white matter and observed an increase in the expression of iron-related proteins in myeloid cells at the lesion rims of MS plaques. qPCR revealed a marked increase of the heme scavenging and degradation machinery of MG under IFN-γ exposure, while OPCs changed to a more iron-inert phenotype with apparent decreased iron handling capabilities under MS-like inflammatory stimulation. Collectively, our data suggest that OL iron loss in MS is mainly due to a decrease in ferritin iron import. Iron accumulation in MCs at rims of chronic active lesions is in part driven by up-regulation of heme import and metabolism, while these cells also actively export ferritin.